2019
DOI: 10.1038/s41598-019-56788-y
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidophilic Molecule Interactions on the Surface of Insulin Fibrils: Cooperative Binding and Fluorescence Quenching

Abstract: Protein aggregation into insoluble fibrillar aggregates is linked to several neurodegenerative disorders, such as Alzheimer’s or Parkinson’s disease. Commonly used methods to study aggregation inhibition or fibril destabilization by potential drugs include spectroscopic measurements of amyloidophilic dye molecule fluorescence or absorbance changes. In this work we show the cross-interactions of five different dye molecules on the surface of insulin amyloid fibrils, resulting in cooperative binding and fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…In some cases, where GA or other polyphenolic compounds displayed a reduction in ThT fluorescence, additional examinations by alternative methods, such as transmission electron microscopy, revealed that such a fluorescence inhibition may be related to interference between the dye and inhibitor 24 . This could be the result of either fluorescence quenching due to molecule interactions or as an inner filter effect, because of the absorbance of ThT emissions by the inhibitor 25 . Despite this, multiple reports consider the reduction of ThT fluorescence as inhibition of aggregation [10][11][12]14,16,17,19,22,26 .…”
mentioning
confidence: 99%
“…In some cases, where GA or other polyphenolic compounds displayed a reduction in ThT fluorescence, additional examinations by alternative methods, such as transmission electron microscopy, revealed that such a fluorescence inhibition may be related to interference between the dye and inhibitor 24 . This could be the result of either fluorescence quenching due to molecule interactions or as an inner filter effect, because of the absorbance of ThT emissions by the inhibitor 25 . Despite this, multiple reports consider the reduction of ThT fluorescence as inhibition of aggregation [10][11][12]14,16,17,19,22,26 .…”
mentioning
confidence: 99%
“…MB shows an inhibitory effect on SOD1 aggregation in a concentration-dependent manner, affecting the nucleation phase (as seen by the increase in lag time). Its effect on the quantity of fibrils formed cannot be determined accurately, as MB is known to partially quench the fluorescence of ThT ( Ziaunys, Mikalauskaite & Smirnovas, 2019 ). Because of the possibility of MB interacting with ThT and affecting both the total fluorescence, as well as aggregation kinetic monitoring, the aggregation reaction was simulateneously tracked by measuring sample absorbance and ThT fluorescence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6E ), showing the dominance of fibrillar material after pre-formed fibril treatment with MB. According to the second hypothesis, ThT and MB interact with each other either in solution or on the surface of SOD1 aggregates, as a similar phenomenon was shown to occur on the surface of insulin fibrils ( Ziaunys, Mikalauskaite & Smirnovas, 2019 ). Such interaction may result in ThT fluorescence quenching.…”
Section: Discussionmentioning
confidence: 96%
“…[ 23 ] This means that any compound which could alter the aggregation process, would have an affinity towards the non‐native protein structures. It has been shown that multiple molecules, such as thioflavin‐T (ThT), Congo red or methylene blue have a high affinity towards the amyloid fibril surface [ 24,25 ] and also affect their rate of aggregation or self‐association. [ 26–28 ] Taking these factors into consideration, it is possible that some of the potential drug molecules would also bind to the surface of amyloid fibrils, while compounds that do not affect aggregation—would not.…”
Section: Introductionmentioning
confidence: 99%